Conceptualization and treatment of borderline personality disorder: a narrative review - Peña-Muñante, Gonzalo Sebastián (2023)
Borderline personality disorder (BPD) is a common mental disorder affecting a significant percentage of individuals worldwide (0.7 % - 5.9 %). However, it is also one of the most challenging disorders to address due to the severe impairment it causes in diagnosed individuals’ social and occupational functioning. Therefore, this review presents various theoretical aspects to broaden the understanding and treatment of BPD. It begins by describing the diagnostic criteria for BPD according to the DSM-5, the psychopathological characteristics based on Millon’s personality theory, and the mechanisms of chronicity. Subsequently, it explores the etiological causes, related clinical syndromes, and the use of third-generation therapies as psychological interventions for BPD. Finally, it presents future lines of research and their implications to contribute to a comprehensive conceptualization of BPD.